Cilostazol Suppresses Aβ-induced Neurotoxicity in SH-SY5Y Cells through Inhibition of Oxidative Stress and MAPK Signaling Pathway - Oguchi, Tatsunori; Ono, Ran; Tsuji, Mayumi; Shozawa, Hidenobu; Somei, Masayuki; Inagaki, Manami; Mori, Yukiko; Yasumoto, Taro; Ono, Kenjiro; Kiuchi, Yuji (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) is a slowly progressive form of dementia, characterized by memory impairment and cognitive dysfunction. AD is mainly characterized by the deposition of amyloid β (Aβ) plaques and intracellular neurofibrillary tangles in the brain, along with neuronal degeneration and high levels of oxidative stress. Cilostazol (CSZ) was recently found to suppress the progression of cognitive decline in patients with stable AD receiving acetylcholinesterase inhibitors. This present study aimed to clarify the mechanism by which CSZ protects neurons from degeneration associated with Aβ(1-42). We used Aβ(1-42) to induce neurotoxicity in human neuroblastoma SH-SY5Y cells. Cells were pretreated with CSZ before co-treatment with Aβ. To evaluate the effect of CSZ on oxidative stress, we examined levels of reactive oxygen species (ROS), nicotinamide adenine dinucleotide phosphate oxidase (Nox) activity, mRNA expression of NOX4, and Cu/Zn-superoxide dismutase, as well as apoptosis biomarkers [MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide), caspase-3 and -9 activities, and staining of annexin V]. We also assayed the activity of mitogen-activated protein kinases (MAPK): p38 MAPK and extracellular signal-regulated kinase1/2 (ERK1/2), and biomarkers of mitochondrial function (Bcl-2, and Bax), and cyclic adenosine monophosphate response element-binding protein (CREB). Aβ-induced oxidative stress (ROS, NOX4 activity, and expression of NOX mRNA), caspase activation (caspase-3 and -9), and p38 MAPK phosphorylation were suppressed by co-treatment with CSZ, but not by ERK1/2 activation. In addition, pretreatment with CSZ suppressed Aβ-induced apoptosis and increased cell viability via suppression of Bax (a proapoptotic protein), upregulation of Bcl-2 (an antiapoptotic protein) and Cu/Zn-superoxide dismutase (a superoxide scavenging enzyme), and phosphorylation of CREB. These findings suggested that CSZ could counteract neurotoxicity through multiple mechanisms, one mechanism involving the attenuation of oxidative stress by suppressing NOX activity and Nox mRNA expression in Aβ-induced neurotoxicity and another involving the anti-neurotoxic effect via the ERK1/2/phosphorylated CREB pathway.